Vertical and interhemispheric links in the stratosphere-mesosphere as revealed by the day-to-day variability of Aura-MLS temperature data - X. Xu; A. H. Manson; C. E. Meek; T. Chshyolkova; J. R. Drummond; C. M. Hall; D. M. Riggin; R. E. Hibbins (Annales Geophysicae, 2009)
The coupling processes in the middle atmosphere have been a subject of intense research activity because of their effects on atmospheric circulation, structure, variability, and the distribution of chemical constituents. In this study, the day-to-day variability of Aura-MLS (Microwave Limb Sounder) temperature data are used to reveal the vertical and interhemispheric coupling processes in the stratosphere-mesosphere during four Northern Hemisphere winters (2004/2005–2007/2008). The UKMO (United Kingdom Meteorological Office) assimilated data and mesospheric winds from MF (medium frequency) radars are also applied to help highlight the coupling processes. In this study, a clear vertical link can be seen between the stratosphere and mesosphere during winter months. The coolings and reversals of northward meridional winds in the polar winter mesosphere are often observed in relation to warming events (Sudden Stratospheric Warming, SSW for short) and the associated changes in zonal winds in the polar winter stratosphere. An upper-mesospheric cooling usually precedes the beginning of the warming in the stratosphere by 1–2 days. Inter-hemispheric coupling has been identified initially by a correlation analysis using the year-to-year monthly zonal mean temperature. Then the correlation analyses are performed based upon the daily zonal mean temperature. From the original time sequences, significant positive (negative) correlations are generally found between zonal mean temperatures at the Antarctic summer mesopause and in the Arctic winter stratosphere (mesosphere) during northern mid-winters, although these correlations are dominated by the low frequency variability (i.e. the seasonal trend). Using the short-term oscillations (less than 15 days), the statistical result, by looking for the largest magnitude of correlation within a range of time-lags (0 to 10 days; positive lags mean that the Antarctic summer mesopause is lagging), indicates that the temporal variability of zonal mean temperature at the Antarctic summer ...